Analisis Pemahaman Konsep Siswa Dalam Menyelesaikan Soal Matematika Menggunakan Alat Peraga Papan Lingpusta - Anditha Cahyo Sujiwo, Dimas; Stefani , Stefani; Lutfiyah, Lutfiyah (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2025)
This research aims to describe students' conceptual understanding when they solve problems using the Lingpusta board teaching aid. Understanding mathematical concepts is the main key in mastering mathematics. Understanding concepts is very important for students after going through the learning process. The ability to understand concepts also requires students to recall concepts that have been studied previously. Understanding concepts means students are able to explain the relationships between concepts and apply concepts flexibly, accurately, efficiently, and precisely to a problem. The Lingpusta board is used to illustrate the concept of sets and their relationships with elements in the universe or universal sets. This research used a qualitative approach with subjects consisting of 2 low-ability students and 2 high-ability students in class VII at Darur-Rahmah Middle School. The research instruments consist of problem-solving questions, students' conceptual understanding tests, and interview guidelines. The results of this research show that students who have high ability to understand the concept can solve the questions well and fulfill the six indicators that have been determined, while students who have low understanding have difficulty in solving the questions given and fulfill the five indicators that have been determined. Keywords: mathematics, library board, concept understanding